Taste and See: Eucharist as Revelation in Phenomenological Perspective - Olson, J.W. (Lexington Books, 2023)
J.W. Olson argues that recent Christian theologies of divine revelation, though often centered on the irreducibility of the incarnation, have not taken incarnality sufficiently into account as the mechanism for the knowledge of God in Christ. Addressing this problem within a secular context in which the viability of religious truth is under increased scrutiny, Olson engages with the phenomenology of Martin Heidegger to suggest that Christian language and belief are shaped at the precognitive level of embodied involvement long before they ever take mental, conceptual form. He then offers an original interpretation of the Eucharist as the material epicenter of Christian epistemology. In the sacrament, Christians are swept up into a dynamic world that reveals itself as the very person of Jesus Christ, so that Christians come to know Christ most fundamentally through the movements of the body. Recasting the parameters for identifying Christ’s sacramental presence, Olson reiterates the Christian focus on the incarnation as not just the medium of God’s self-revelation but as the very content of Christian faith. Christ is known in act, and so God is revealed where Christ lives in us.